2017
DOI: 10.1007/s10803-017-3081-9
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder Symptoms in Infants with Fragile X Syndrome: A Prospective Case Series

Abstract: No studies to date have prospectively examined early autism spectrum disorder (ASD) markers in infants with fragile X syndrome (FXS), who are at elevated risk for ASD. This paper describes the developmental profiles of eight infants with FXS from 9 to 24 months of age. Four meet diagnostic criteria for ASD at 24 months of age, and four do not. Trends in these case studies suggest that early social-communicative deficits differentiate infants with and without later ASD diagnoses in ways that are similar to late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 52 publications
(83 reference statements)
2
33
1
12
Order By: Relevance
“…Motor function in FXS gradually diverges from a typical trajectory between infancy and toddlerhood 48 and atypical motor behaviors, such as stereotypies, are hallmark features of FXS from early in life. 4,49 We did not find that the SCP or other putative motor pathways were associated with NVDQ. Further analysis into this issue revealed that the visual reception component appeared to drive the association between uncinate FA and NVDQ.…”
Section: Discussioncontrasting
confidence: 60%
“…Motor function in FXS gradually diverges from a typical trajectory between infancy and toddlerhood 48 and atypical motor behaviors, such as stereotypies, are hallmark features of FXS from early in life. 4,49 We did not find that the SCP or other putative motor pathways were associated with NVDQ. Further analysis into this issue revealed that the visual reception component appeared to drive the association between uncinate FA and NVDQ.…”
Section: Discussioncontrasting
confidence: 60%
“…So, despite evidence of early cognitive deficits [Jeste et al, ], the social communication development of many infants with TSC does not deviate from typically developing infants in a substantial way, at least early in life. This finding lies in contrast with studies of other syndromic forms of ASD, such as Fragile X Syndrome, where infants who did not develop ASD evidenced elevations on the AOSI at 9 months [Hogan et al, ]. The spared social communication development of TSC/no ASD infants, therefore, provides a unique opportunity to examine resilience, or the biological, behavioral, and environmental factors that may protect some infants with TSC from adverse neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…Parents completed the Infant Behavior Questionnaire (IBQ [ 42 ]), a parent-report measure that comprises 14 subscales grouped into three overarching factors labelled Surgency (the child’s tendency to show excitement, positive affect, and approach), Negative Affect (the child’s tendency to cry, be avoidant, or otherwise fussy), and Effortful Control (the child’s ability to regulate their mood and behaviour) [ 42 , 43 ]. Parents of infants at high familial risk for ASD completed the original form of the IBQ-R [ 44 ]; parents of infants with NF1 completed the short form [ 42 ].…”
Section: Methodsmentioning
confidence: 99%